The effect of photocatalyst effect of titanium dioxide anatase on heat polymerized acrylic resin plate towards the growth of Candida albicans colonies: Pengaruh efek fotokatalis titanium dioxide anatase pada plat resin akrilik polimerisasi panas terhadap pertumbuhan koloni Candida albicans - Teguh Tri Widodo; Claudia Sekar Ayu M (Makassar Dental Journal, 2022)
Background: In general, removable denture are made from polymethyl methacrylate (PMMA) resin as the base material. This material has a drawback, namely that it is often attached to micro-organisms such as the fungus Candida albicans. Nanoparticle materials such as titanium dioxide (TiO₂) have antimicrobial properties, especially against C.albicans because it has photocata-lytic properties that can inhibit the growth of C.albicans colonies. Objective: To determine the effect of applying titanium di-oxide to heat polymerized acrylic resin (HPAR) plates towards the growth of C.albicans colonies. Methods: A true experimen-tal laboratory study using the HPAR plate as the object of research which was divided into the control group and the 1%, 2%, and 3% titanium dioxide-added groups. Data were analyzed using one-way Anova Welch. Results: There was an effect of add-ing titanium dioxide on the base of HPAR RD towards the growth of C.albicans colonies. Statistical tests showed significant re-sults (p=0.000; <0.05)). In the test between the titanium dioxide 1%, 2%3% and control groups, there were significant diffe-rences. Conclusion: The application of titanium dioxide to the base of HPAR RD reduced the growth of C.albicans colonies.